Ocean dynamics: the work of the sea. - Boyer, Robert Ernst, 1929- (Chicago : Encyclopaedia Britannica Educational Corporation, 1981)
Investigates ocean movement, from the obvious effects of waves on the land and the weather, to the less apparent, but equally profound, forces deep within the oceans.
Keywords: Ocean waves